In vitro potential control of white root fungus in nutmeg (Myristica fragrans) based on botanical fungicide of coconut shell liquid smoke - CHAIRUDIN, CHAIRUDIN; SUBANDAR, IRVAN; AGUSTINUR, AGUSTINUR; MAULIDIA, VINA (Jurnal Natural, 2024)
Nutmeg (Myristica fragrans) is spice plant which has an important position as a source of essential oils. An important problem in nutmeg cultivation is white root disease which can reduce nutmeg production. Until now, white root disease is still a problem in nutmeg plantations in South Aceh district. One of the solution that can be explored as an environmentally friendly control measure is to use the botanical fungicide coconut shell liquid smoke. This research aims to determine the potential of coconut shell liquid smoke in controlling white root fungus in vitro. The research was carried out in the Plant Protection Laboratory, Faculty of Agriculture, Teuku Umar University. The research design used was a non-factorial Completely Randomized Design (CRD) consisting of nine levels of liquid smoke concentration treatment; control 0%, 0.5%, 1%, 2%, 3%, 4%, 6%, 8%, 10%. Each treatment involved three replications. Data analysis was carried out using analysis of variance and Tukey's least significant difference (HSD) test.The research stages carried out consisted of producing coconut shell liquid smoke, isolating white root fungus from the roots of infected nutmeg plants and potential assay of liquid smoke in inhibiting the growth of white root fungus. In vitro bioassay result showed that liquid smoke treatment 3% was the best treatment because it was the lowest concentration causing total inhibition of the growth of white root fungus.